Bank Ownership : Trends and Implications - Cull, Robert (IMF Working Papers; Working Paper ;, 2017)
This paper presents recent trends in bank ownership across countries and summarizes the evidence regarding the implications of bank ownership structure for bank performance and competition, financial stability, and access to finance. The evidence reviewed suggests that foreign-owned banks are more efficient than domestic banks in developing countries, promote competition in host banking sectors, and help stabilize credit when host countries face idiosyncratic shocks. But there are tradeoffs, since foreign-owned banks can transmit external shocks and might not always expand access to credit. The record on the impact of government bank ownership suggests few benefits, especially for developing countries.